2011
DOI: 10.1186/1471-2466-11-55
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers' perceived adequacy of support in end-stage lung disease: results of a population survey

Abstract: BackgroundEnd-stage lung disease (ESLD) is a frequent cause of death. What are the differences in the supports needed by caregivers of individuals with ESLD at end of life versus other life-limiting diagnoses?MethodsThe South Australian Health Omnibus is an annual, random, face-to-face, cross-sectional survey. In 2002, 2003 and 2005-2007, respondents were asked a range of questions about end-of-life care; there were approximately 3000 survey participants annually (participation rate 77.9%). Responses were stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…ACP is recommended in COPD [31] and lung cancer [32]. Our findings are similar to a study showing that family caregivers need knowledge about the progression of the disease [33] and supporting practical help, especially administration of oxygen [8].…”
Section: Discussionsupporting
confidence: 85%
“…ACP is recommended in COPD [31] and lung cancer [32]. Our findings are similar to a study showing that family caregivers need knowledge about the progression of the disease [33] and supporting practical help, especially administration of oxygen [8].…”
Section: Discussionsupporting
confidence: 85%
“… 1 2 The burden of this distressing symptom however remains devastatingly high for people who experience it and their caregivers. 3 It is not only a highly feared symptom in those approaching end of life 4 but unlike many other symptoms, breathlessness typically worsens, despite treatment, as death approaches. 5 6 …”
Section: Introductionmentioning
confidence: 99%
“…All but one qualitative study used interviews to gather data; 5 , 18 , 27 – 32 , 36 – 39 , 43 , 44 focus groups were utilised in the remaining paper. 33 Quantitative studies were observational, with most being cross-sectional; 34 , 40 – 42 , 46 the one exception to this was Ross and Graydon, 45 who employed case-control. Carers were more likely to be female, with 15 papers either recruiting more women than men or specifically targeting female participants.…”
Section: Resultsmentioning
confidence: 99%
“…Findings suggest that COPD carers encounter considerable barriers to accessing services. Carers appear to struggle with accessing financial assistance, 5 , 13 , 29 , 32 , 42 – 44 alternative sources of care for the patient, 31 , 34 , 42 support from social services, 13 , 46 adequate specialist healthcare services, 31 spiritual support 40 , 42 and affordable, consistent home help. 18 , 34 , 37 – 39 , 42 , 43 Studies also revealed significant difficulties in accessing equipment and housing adaptations.…”
Section: Resultsmentioning
confidence: 99%